EKO-TEOLOGI AL-QUR`AN: SEBUAH KAJIAN TAFSIR AL-QUR`AN DENGAN PENDEKATAN TEMATIK - Wardani, Mulyani dan (Fakultas Ushuluddin dan Humaniora UIN Antasari Banjarmasin, 2013)
One of the important issues facing the global and human was the environmental issue. This paper discussed a solution to this global crisis from the perspective of al-Qur`an about theology environment (eco - theology). By applying a thematic approach (mawdh') in the study of Tafseer al-Qur`an, this paper came to an important conclusion. First, in view of universe al-Qur`an was referred to as evidence of God's creation creativity. Nature was also created as a sign of his power. Therefore, the universe was created had a purpose (bil hikmah) (bi al-haq), not in vain (falsehood). Second, al-Qur`an taught theological principles in the maintenance of nature, namely that the Earth was only inherited theological promised by His servants the righteous course, the relationship management of nature (taskhr) with a value of tawhid, the need to pay attention to the balance of the cosmos and the principle economic in nature management, the necessity of the earth